Decentralized by Design, Centralized by Necessity: The Blockchain-Surveillance Dilemma - Vahid Mirzajani Harandi (Blockchain in Healthcare Today, 2026)
Disease surveillance systems face delays in data collection, validation, and reporting at various levels, which undermines early detection and rapid response. Blockchain technology, as a transparent and immutable architecture, can accelerate the flow of epidemiological data and increase trust among actors, but the transition from idea to practical tool requires an analysis of requirements and limitations. This article examines the key challenges of applying blockchain in disease surveillance in two axes: first, governance challenges, data sovereignty, and the inherent conflict of decentralized architecture with epidemiological requirements and privacy laws; second, technical, infrastructural, and operational challenges such as digital identity, interoperability, communication limitations, economic model, and security vulnerabilities. Therefore, the conclusion shows that blockchain can only contribute to transparency and traceability in the form of permissioned/consortium networks with verified identity, and its true effectiveness depends on feasibility studies, piloting, and intelligent combination with data exchange standards and international cooperation.Key takeaways• Blockchain can potentially improve transparency, traceability, and trust in surveillance systems.• Real effectiveness requires feasibility studies, pilots, and detailed evaluations.• The future of patient care lies in a combination of digital technologies, data exchange standards, andinternational collaboration.